A Analisis Prediksi Kebangkrutan dan Deteksi Kecurangan Laporan Keuangan pada Perusahaan Subsektor Farmasi dan Kesehatan yang Terdaftar di BEI Periode 2021-2024 - Windayani, Sang Putu; Ni Luh Gede Erni Sulindawati; Sunitha Devi (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to analyze bankruptcy prediction, detect financial statement fraud, and examine the relationship between predicted bankruptcy and financial statement manipulation. It uses a descriptive quantitative approach with secondary data from the financial reports of pharmaceutical and health subsector companies listed on the IDX for the 2021–2024 period. The sample includes 7 companies. The results show that no companies are indicated to be bankrupt based on the Grover model. However, 4 companies are detected to have manipulated their financial statements according to the Beneish M-Score. Interestingly, although there are no signs of bankruptcy, one company has poor financial ratios and is also detected to have engaged in manipulation. These findings suggest that financial statement fraud can still occur even when bankruptcy is not imminent. This indicates that some companies may attempt to maintain a stable financial image through manipulation, despite not showing financial distress based on bankruptcy models.